САМОВОЛЬНО ВОЗВЕДЕННЫЕ ГОРОДА - United Nations (United Nations, 2009)
Informal settlements are often characterized as “illegal” residential formations lacking basic infrastructure, security of tenure and adequate housing. This book describes how more than 50 million people in the United Nations Economic Commission for Europe (UNECE) region have come to live in informal settlements and examines the main characteristics of the phenomenon. It also provides policy recommendations based on case studies and initiatives implemented in the region, with varying degrees of success. It concludes that there is no “one-size-fits-all” solution, as informal settlements are the product of complex socio-political processes that differ significantly from country to country and from region to region.